Atrial fibrillation in heart failure: drugs or ablation?. (21st April 2023) - Palmas, Francesco; Noviello, Cecilia; Bo, Mario
Abstract: Atrial fibrillation (AF) and heart failure (HF) frequently coexist and mutually exert negative influences with important clinical implications. Although there is evidence that restoring and maintaining sinus rhythm may have favourable clinical effects in patients with HF, there is no evidence of a survival benefit with pharmacological antiarrhythmic intervention compared with a heart rate control strategy. In these patients, transcatheter ablation (CA) of AF represents a procedure with an excellent safety profile in centres with expertise and a high volume of interventions. However, in the absence of definite evidence of benefit on major clinical end-points that can be generalized to the heterogeneous population with AF and HF, the option of CA should be discussed and shared with the patient, and mainly considered in patients with conditions that are associated with a greater prospect of clinical benefit, such as 'young' age (65–70 years), good health conditions and few or no comorbidities, recent onset of HF and AF (especially if with high heart rate), left atrial volume not excessively compromised (<55 mm in diameter), and without evidence of substantial fibrotic remodelling, left ventricular ejection fraction (LVEF) >25%, including HF with preserved EF (HFpEF).